PERBEDAAN MUTU ORGANOLEPTIK DAN PROTEIN ROLLADE IKAN BLEBERAN (Thryssa sp.) SEBAGAI SUMBER PROTEIN BALITA STUNTING - Meriwati Mahyuddin (Poltekkes Kemenkes Bengkulu, 2026)
Background: Nutritional disorders such as stunting, wasting, and underweight are still serious problems in Indonesia that impact the quality of children's growth. Bleberan fish (Thryssa sp.) is a local marine resource in the coastal area of ​​Bengkulu, which is rich in animal protein and iron, but its utilization as nutritious food for children has not been optimal. Objective: This study aims to develop bleberan fish rollade products as an alternative functional food that has high nutritional value and good acceptability to stimulate the growth rate of children with nutritional disorders. Method: This type of research is research and development (R&D) conducted at the Nutrition Food Laboratory of the Ministry of Health Polytechnic of Bengkulu. Products without added vegetables or F0 (Original) were tested in the form of steamed and fried, which were previously dipped in a solution of wheat flour, paint, and breadcrumbs before being fried. Data on energy and macronutrient composition were collected through nutrient content estimation using TKPI and organoleptic tests (color, aroma, texture, and taste) by 40 nutrition student panelists using a hedonic scale. Results: Analysis showed that the nutritional content per serving (50 grams) ranged from 147–170 kcal of energy and 10–11 grams of protein. Based on organoleptic testing, fried roulade was the most popular overall, with a 52.5% preference rating, and was superior in color (67.5%) and taste (60%). The Mann-Whitney statistical test showed significant differences (p < 0.05) in panelist preference for all product attributes based on different presentation techniques. Conclusion: Bleberan fish rollade has great potential as a functional food to address nutritional disorders due to its high protein content (18.75 g/100 g) and iron (1.71 mg). The original bleberan fish formulation is recommended as the primary choice due to its stable organoleptic quality and highest acceptability.